2019
DOI: 10.1063/1.5112835
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of the liquid organic hydrogen carrier system 2-methylindole/2-methylindoline/2-methyloctahydroindole on Pt(111)

Abstract: Among other N-heterocycles, indole and its substituted derivatives, such as methylindoles, are considered promising Liquid Organic Hydrogen Carriers (LOHCs) for the storage of renewable energy. We used X-ray photoelectron spectroscopy (XPS), temperature programmed desorption (TPD), and density-functional theory (DFT) to investigate the low temperature adsorption and consecutive dehydrogenation reaction during heating of 2-methylindole, 2-methylindoline, and 2-methyloctahydroindole on Pt(111) and their viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Given our earlier assignment of that shoulder to carbon located next to the cationic N + , the diminishing of this species lines up well with the disappearance of quaternary ammonium. The broadening of the main feature toward the higher BE side might be a consequence of carbon centers now bound to a nitrogen atom in a molecular amine, which would be expected around 285 eV. , The broadening toward the lower BE side is a bit more unclear but may result from the formation of electron-rich carbon atoms, such as e.g. elemental carbon, frequently observed as a consequence of coking on metal surfaces, or metal carbides. In principle, alkenes and other unsaturated compounds would result in a shoulder at a similar position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our earlier assignment of that shoulder to carbon located next to the cationic N + , the diminishing of this species lines up well with the disappearance of quaternary ammonium. The broadening of the main feature toward the higher BE side might be a consequence of carbon centers now bound to a nitrogen atom in a molecular amine, which would be expected around 285 eV. , The broadening toward the lower BE side is a bit more unclear but may result from the formation of electron-rich carbon atoms, such as e.g. elemental carbon, frequently observed as a consequence of coking on metal surfaces, or metal carbides. In principle, alkenes and other unsaturated compounds would result in a shoulder at a similar position.…”
Section: Resultsmentioning
confidence: 99%
“…The broadening of the main feature toward the higher BE side might be a consequence of carbon centers now bound to a nitrogen atom in a molecular amine, which would be expected around 285 eV. 68,69 The broadening toward the lower BE side is a bit more unclear but may result from the formation of electronrich carbon atoms, such as e.g. elemental carbon, frequently observed as a consequence of coking on metal surfaces, or metal carbides.…”
Section: On-particle Conversion Of Ionicmentioning
confidence: 99%
“…Cyclic alkanes and N-heterocyclic species are of special interest due to their stability and high energy density. Cycloalkane LOHC systems such as cyclohexane/benzene are good models for mechanistic studies. , Others that are viable on the industrial scale include perhydro-dibenzyl toluene/dibenzyl toluene , and methylcyclohexane/toluene. , Although the cyclohexane/benzene system (eq ) is not very useful in the context of scaling up owing to the carcinogenic properties of benzene, it is often used as a model due to its relatively easy access to mechanistic studies and has been investigated in the context of reactant/product separation. , N-Heterocycle couples such as piperidine/pyridine (eq 2, and derivatives), octahydroindole/indole, and perhydrophenazine/phenazine (eq 3) are all viable substrates for stable hydrogen storage. N-Heterocycles have the added benefits of relatively better biodegradability, low volatility, and more efficient hydrogen liberation …”
Section: Introductionmentioning
confidence: 99%
“…Previously, the detailed mechanism of LOHC dehydrogenation was investigated using model catalysts such as well-ordered Pt(111) and Pd(111) single crystals 6,[11][12][13][14] and well-defined Pt and Pd supported nanoparticles. [15][16][17] It was found that dehydrogenation of both homocyclic and N-heterocyclic LOHCs involves multiply dehydrogenated intermediates.…”
Section: Introductionmentioning
confidence: 99%